142 Accumulation of cardiomyocyte senescence following ischaemia-reperfusion injury (IRI); a potential therapeutic target?. (June 2018) - Dookun, Emily; Walaszczyk, Anna; Redgrave, Rachael; Tual-Chalot, Simon; Yausep, Oliver; Spyridopoulos, Ioakim; Owens, Andrew; Arthur, Helen; Richardson, Gavin; Passos, Joao
Abstract : Introduction: Myocardial infarction (MI) is a prominent cause of morbidity and mortality globally. While reperfusion via primary percutaneous coronary intervention is the gold-standard therapy, it can lead to the phenomenon ischemia-reperfusion injury (IRI), characterised by progressive remodelling and heart failure. Little is understood regarding to the mechanisms driving IRI, however, increased oxidative stress is known to play a role. Our previous studies demonstrate that during ageing increased oxidative stress drives telomere associated DNA damage foci (TAF) induced cardiomyocyte senescence, which is directly associated with a hypertrophic phenotype. Furthermore senescent cardiomyocytes express a pro-fibrotic profile; in particular an up-regulation of TGF-β expression. We now hypothesise that cardiomyocyte senescence contributes to remodelling subsequent to MI and IRI via similar mechanisms, and as such represents a potential therapeutic target. Methods: Young three month old mice underwent 60 min surgical ligation of the left anterior descending coronary artery to mimic MI followed by reperfusion. Histological analysis at numerous time points post-MI for several senescence markers was performed. Results and conclusions: In support of our hypothesis, we have observed that within the surviving myocardium, proximal to the infarct region, cardiomyocytes acquire a senescent-like phenotype. This is demonstrated by an increase in senescence markers including SA-β-Gal, p21 and p16, in addition to an accumulation of TAF. As well as this we verified that mice displayed classical pathophysiological aspects related to MI. Using in vitro studies and transgenic mouse models we aim to better understand the biology underlying cardiomyocyte senescence, and to establish the mechanisms underlying senescence contribution to remodelling. Furthermore we aim to ascertain if modulation or clearance of cardiomyocyte senescence promotes regeneration and improves outcome following IRI.